2020
DOI: 10.3390/app10020569
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Screening and Machine Learning to Predict the Computation-Ready, Experimental Metal-Organic Frameworks for CO2 Capture from Air

Abstract: The rising level of CO2 in the atmosphere has attracted attention in recent years. The technique of capturing CO2 from higher CO2 concentrations, such as power plants, has been widely studied, but capturing lower concentrations of CO2 directly from the air remains a challenge. This study uses high-throughput computer (Monte Carlo and molecular dynamics simulation) and machine learning (ML) to study 6013 computation-ready, experimental metal-organic frameworks (CoRE-MOFs) for CO2 adsorption and diffusion proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…A procedure to reduce the cost of large-scale screening studies of adsorbent materials such as MOFs is to prescreen structures using properties that are fairly inexpensive to calculate. 20,[54][55][56][57] These include geometric features, such as LCDs, pore volume, fractional free volume (FFV), and accessible surface areas, as well as energetic features such as heats of adsorption and Henry's constants at the infinite dilution condition. While these can be useful in informing behavior of adsorbent materials in general, the complex mechanisms through which water adsorption occurs raise a question as to whether these features can be predictive for adsorption properties and help identify interesting materials.…”
Section: Prescreening Mof Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…A procedure to reduce the cost of large-scale screening studies of adsorbent materials such as MOFs is to prescreen structures using properties that are fairly inexpensive to calculate. 20,[54][55][56][57] These include geometric features, such as LCDs, pore volume, fractional free volume (FFV), and accessible surface areas, as well as energetic features such as heats of adsorption and Henry's constants at the infinite dilution condition. While these can be useful in informing behavior of adsorbent materials in general, the complex mechanisms through which water adsorption occurs raise a question as to whether these features can be predictive for adsorption properties and help identify interesting materials.…”
Section: Prescreening Mof Structuresmentioning
confidence: 99%
“…Indeed, these have been commonly employed in the prescreening of materials as reported in numerous studies, mainly concerning molecules which are simpler to simulate such as CH 4 and CO 2 . 20,[54][55][56][57] However, insights into their predictive abilities for water adsorption behavior remain rather limited to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that purpose, the CO 2 capture potential of 6013 CoRE MOFs from air was predicted using four different ML algorithms (back-propagation neural network (BPNN), DT, RF, and SVM) with structural descriptors such as pore sizes, volumetric surface area, and heat of adsorption ( Q st ). 72 To train the models, a maximum of 1000 MOFs were used while the remaining MOFs were used for the validation of the ML models. The ML model built with RF algorithm was reported to have the best prediction performance of CO 2 adsorption selectivity ( R 2 = 0.98) for the validation set and the relative importance analysis revealed that Q st is the most important parameter to predict adsorption selectivity for CO 2 .…”
Section: Gas Separation Performances Of Mofsmentioning
confidence: 99%
“…The development of efficient CO 2 abatement systems is widely pursued as a means of mitigating the detrimental effects of global warming [1]. Currently, intense research efforts are focusing on CO 2 capture technologies, such as membrane processes [2], adsorption systems [3], and materials- [4,5] and solvent-based absorption/desorption processes [6]. The latter represents a technology with significant potential, which has been demonstrated even in large-scale plants [7,8].…”
Section: Introductionmentioning
confidence: 99%